PARTIAL EPITHELIAL-TO-MESENCHYMAL TRANSITION AND T CELL-MEDIATED INFLAMMATION IN BENIGN NEPHROSCLEROSIS AND DIABETIC NEPHROPATHY. (April 2021) - Nordbø, Ole Petter; Landolt, Lea; Eikrem, Øystein; Scherer, Andreas; Leh, Sabine; Palmer, Jessica Furriol; Apeland, Terje; Marti, Hans-Peter
Abstract: Objective: We wanted to investigate to which degree patients with benign nephrosclerosis (BN) or type 2 diabetic nephropathy (T2DN) present inflammation and/or partial epithelial-to-mesenchymal transition (EMT) in renal formalin-fixed and paraffin-embedded (FFPE) biopsies. Design and method: The following FFPE kidney biopsies from adult patients (n = 6 biopsies per group) were analysed: BN, T2DN and normal-appearing renal biopsy tissue (Ctrl). Messenger RNA was purified from whole tissue sections (10 mm) and subjected to RNA sequencing. Immunohistochemistry (IHC) was performed on 3-mm FFPE sections. Results: Dimention reduction with principal component analysis showed a distinct separation between diseased and Ctrl tissues. Further, the BN expression profile overlapped significantly with T2DN. More detailed analysis of gene expression profiles revealed the activation of T-helper type 1 (TH1) and CD8 cytotoxic T-cell (CTL) signatures and the upregulation of the complement system in both diseases. IHC validated CD8 and CD4 cells as well as complement component 3 and the terminal complement complex C5b-9. We show upregulation of EMT- related genes and validated increased abundance of AXL and Vimentin by IHC. Conclusions: BN and T2DN tissues show a phenotype related to TH1, CD8 CTL inflammation and the complement system. Further, processes related to EMT were upregulated in both diseases.